90.2k views
10 votes
(x + 4)(3x + 2) = ____________ 2. (3x – 1)(2x – 5) = ____________ 3. (5x + 2)(2x + 5) = ____________ 4. (4x – 1)(2x + 7) = ____________ 5. (2x + 6)(4x + 8) = _n​

User Elkdee
by
5.1k points

1 Answer

4 votes

Answer:

o 1)


(x + 4)(3x + 2) \\ \\ (x)(3x) + (x)(2) + (4)(3x) + (4)(2) \\ \\ = 3 {x}^(2) + 2x + 12x + 8 \\ = 3 {x}^(2) + 14x + 8

__o__o___

o 2)


(3x - 1)(2x - 5) \\ \\ (3x)(2x) + (3x) ( - 5)+ ( - 1)(2x) + ( - 1)( - 5) \\ \\ = 6 {x}^(2) - 15x - 2x + 5 \\ \\ = 6 {x}^(2) - 17x + 5

__o__o___

o 3)


(5x + 2)(2x + 5) \\ \\ = (5x)(2x) + (5x)(5) + (2)(2x) + (2)(5) \\ \\ = 10 {x}^(2) + 25x + 4x + 10 \\ \\ = 10 {x}^(2) + 29x + 10

__o__o__

o 4)


(4x - 1)(2x + 7) \\ \\ = (4x)(2x) + (4x)(7) + ( - 1)(2x) + ( - 1)(7) \\ \\ = 8 {x}^(2) + 28x - 2x - 7 \\ \\ = 8 {x}^(2) + 26x - 7

__o__o___

o 5)


(2x + 6)(4x + 8) \\ \\ = (2x)(4x) + (2x)(8) + (6)(4x) + (6)(8) \\ \\ = 8 {x}^(2) + 16x + 24x + 48 \\ \\ = 8 {x}^(2) + 40x + 48

User Gedweb
by
5.0k points